Using microorganisms for a sustainable agriculture in Mexico: considerations and challenges - Cruz Cardenas, Carlos Ivan; Zelaya Molina, Lily X.; Sandoval Cancino, Gabriela; de los Santos Villalobos, Sergio; Rojas Anaya, Edith; Chávez Díaz, Ismael Fernando; Ramirez, Santiago Ruiz (Revista Mexicana de Ciencias Agrícolas, 2021)
Numerous plant species of agricultural interest establish symbiosis with soil microorganisms, such as microorganisms that promote plant growth, which provide great benefits because they help to reduce the excessive use of fertilizers and pesticides used in agricultural production. Currently, Mexican agriculture is looking for environmentally friendly fertilization alternatives. That is why sustainable agriculture practices can only be successful when producers have all the means to implement them properly. This essay addresses issues on the considerations and challenges for the development of a sustainable agriculture in Mexico through the use of beneficial microorganisms, and it presents the current and future outlook on their use taking into account the benefit to the producer.
Keywords: biofertilizers; microorganisms in the soil; sustainability